Integrasi Frame Work Risk and Insurance Management Society (RIMS) dalam Analisis Kematangan Implementasi Manajemen Risiko (Studi Kasus: PLTA Maninjau) - Taufik; Ahmad Fauzan (Jurnal Optimasi Sistem Industri, 2013)
Indonesia electrical energy consumption growth that reached 9.2% per year requires every plant to always pursue consistent and sustainable improvement to be able to cope with the growth. Maninjau Hydropower is one of the assets of strategic energy resources to meet the electrical energy supply, especially for the southern Sumatera region. Risk management in Maninjau hydropower take place without any standard of measurement standards, so management and risk management actors do not have an overview and guide to improve the performance of the risk management activities. In this study, a standard measure used is to measure the level of maturity of the risk management implementation using the framework of the Risk and Insurance Management Society (RIMS) for Enterprise Risk Management (ERM). Measurements carried out for the realization of the value and the expected value of risk management implementation in Maninjau hydropower, as well as designing the evaluation chart implementation of risk management by integrating Key Risk Indicators (KRI) from the expected value. Based on the results of the measurements made, it was found that the actual implementation of risk management in Maninjau hydropower located on the third level (repeatable), while the implementation of the expectation value is found to be at the highest level (leadership), and the percentage achieving overall expectation value has reached 62%. The draft also raises the risk evaluation chart 15 Key Risk Indicators to be achieved by Maninjau hydropower to achieve the expected value at the leadership level.